Hospital Marketing Strategy Development Using SWOT, IFE, and EFE Analysis - Rizkaputra, Fergiawan Alfianto; Pratama, Alun; Mulyati, Tatik; Sitegar, Muhammad Arief (LifeSciFi, 2026)
This study is motivated by the importance of formulating an appropriate marketing strategy in response to the dynamic competition within the healthcare sector, particularly at PKU Muhammadiyah Mayong Hospital. The objective of this research is to analyze the role of internal and external environmental factors in the development of the hospital’s marketing strategy. The study employs comparative research design with a mixed methods approach. Data were collected through interviews and questionnaires and analyzed using SWOT analysis, supported by the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The findings indicate that internal strengths include superior facilities, comprehensive human resources, promotional discounts, and structured financial management, while weaknesses involve limited parking facilities and a high financial dependence on BPJS (National Health Insurance). Externally, opportunities arise from potential collaborations with surrounding companies and the availability of trained medical personnel, whereas threats include the planned construction of a new hospital in the Mayong area and difficulties in collecting incomplete patient payments. The IFE score of 2.76 and EFE score of 2.71 position the hospital in Quadrant I, indicating that a growth-oriented strategy is the most appropriate approach.